2015
DOI: 10.1002/elps.201500021
|View full text |Cite
|
Sign up to set email alerts
|

CE‐MS‐based serum fingerprinting to track evolution of type 2 diabetes mellitus

Abstract: Development of type 2 diabetes mellitus (T2DM) is preceded by insulin resistance (IR), which may evolve to impaired fasting glucose (IFG) and/or impaired glucose tolerance (IGT). IFG and IGT are considered as prediabetic states (PD). Prediabetes indicates the high risk for the future development of diabetes, it is estimated that up to 70% of prediabetics eventually develop T2DM. The risk of T2DM development is increased in overweight (OW) and obese (OB) people; however normal weight (NW) individuals also suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…). Interestingly, AA are increased in blood of T2DM patients , whilst in the present study we observed their decrease in AH of diabetics. Similar phenomenon can be noticed for other group of metabolites closely related to T2DM, acylcarnitines.…”
Section: Resultscontrasting
confidence: 54%
“…). Interestingly, AA are increased in blood of T2DM patients , whilst in the present study we observed their decrease in AH of diabetics. Similar phenomenon can be noticed for other group of metabolites closely related to T2DM, acylcarnitines.…”
Section: Resultscontrasting
confidence: 54%
“…The analyte/sheathliquid mass flow rates ratio determines analyte dilution and influences the sensitivity of the analysis. The sheath‐flow interfaces with several μL/min flow rates represent very powerful tools for extensive clinical and biological studies due to a reasonable robustness and reproducible results at interlaboratory level . However, the use of low sheath‐flow interfacing with electrokinetically pumped sheathliquid is on its rise nowadays.…”
Section: Development Of Methodology and Instrumentationmentioning
confidence: 99%
“…CE‐MS methodologies have been developed for metabolomic profiling at various research and diagnostic areas: discovery of diagnostic biomarkers of early stages of Alzheimer's disease in serum ; discovery of potential hepatocellular carcinoma biomarkers in serum ; metabolomic approach to study mechanism of action and resistance of miltefosine (hexadecylphosphocholine) in Leishmaniasis to obtain a broad picture of metabolic changes in the parasite ; investigation of potential biomarkers of fatigue identified by plasma metabolome analysis in rats as a model method for the clinical diagnosis of chronic fatigue in humans ; metabolomic identification of biomarker pattern for early diagnosis of hepatocellular carcinoma ; quantitative metabolome profiling of the kynurenine pathway in influenza‐associated encephalopathy in serum ; serum fingerprinting to track evolution of type 2 diabetes mellitus . Kok et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Importantly, CE also gives complementary information to HILIC [13], as well as, significantly better peak shape in many cases. It is therefore not surprising that CE-MS has already been considered for multiple metabolomics studies covering several applications, from aging [19], amino acid analysis [20,21] [46][47][48][49][50][51][52][53], CVD [54][55][56][57][58], diabetes [59][60][61][62][63][64][65], lifestyle [61][62][63][64][65][66][67][68][69][70][71], kidney disease [72,73], liver disease [74][75][76][77][78][79][80][81][82], the microbiome [83][84]…”
Section: Current Advantages and Biotechnology Applicationsmentioning
confidence: 99%